Linguistic Contribution of Northern Sotho to Sepitori: Perspectives of Speakers of the Language brought up in Tshwane, South Africa - Lebogang M. Madingwaneng; Thabo Ditsele (E-Journal of Humanities, Arts and Social Sciences)
Various scholars indicated that Sepitori resulted from language contact in Tshwane, especially between Northern Sotho and Setswana, which are mutually intelligible. Previous research has focused on the influence of Sepitori on the standard varieties of Northern Sotho and Setswana, and not the other way around and this was a gap in research, which needed to be addressed. This study looked at how Northern Sotho contributed to the development of Sepitori by establishing lexical items, which were drawn from Northern Sotho. The first set of data was gathered from YouTube by extracting statements with Sepitori lexical items; the statements were said by Sepitori-speaking comedians. After that, the statements were discussed with 16 participants to establish whether they regarded them as Sepitori lexical items with origins from Northern Sotho, be it the standard variety or non-standard varieties referred to as dialects; their responses constituted the second set of data. Participants confirmed that Sepitori lexical items which were before them originated from Northern Sotho. Interestingly, they were unaware that there are lexical items which Northern Sotho shared with Setswana and Southern Sotho because they only attributed such to Northern Sotho, and that demonstrated their limited knowledge of Setswana and Southern Sotho. The study has demonstrated that Northern Sotho is one of the most significant languages in the development of Sepitori, the other being Setswana. This study has the potential to encourage more researchers to conduct research on non-standard varieties spoken in South Africa particularly as they continue to gain traction in the linguistic landscape of South Africa.